A Case of Congenital Infantile Fibrosarcoma of the Bowel Presenting as a Neonatal Intussusception. Issue 12 (1st November 2017) - Obayashi, Juma; Koizumi, Hirotaka; Hoshikawa, Masahiro; Wakisaka, Munechika; Fujikawa, Atsuko; Kitagawa, Hiroaki; Takagi, Masayuki
Abstract : Neonatal intussusception of the intestinal tract is rare. However, most neonatal intussusceptions have an organic lead point. For the lead point to be a neoplasm is extremely rare. We report a case that presented with neonatal intussusception with a congenital infantile fibrosarcoma as the lead point. The detection of ETV6‐NTRK3 gene fusion was useful, although the definitive diagnosis was achieved by a comprehensive evaluation including this gene analysis, standard histology and immunohistochemistry. Neonatal intussusception should be suspected to be caused by a neoplasm. If pathological diagnosis is difficult, molecular analysis should be utilized to diagnose congenital infantile fibrosarcoma.